Screening of diseases transmissible by blood in recipients prior to transfusion at a university hospital in the northeast of Brazil - Carrazzone,Cristina F. V. (2006)
The Brazilian Ministry of Health has made tests for HIV1 and HIV2, HTLV I and HTLV II, HCV, HBV, T. cruzi, T. pallidum and Plasmodium in endemic areas, mandatory for all blood collection bags used in the country. However, blood-borne infectious diseases are not investigated in blood recipients before transfusion. For this study, a serological evaluation of recipients before transfusion was carried out. Prior to transfusion, serum samples from 159 blood recipients were analyzed using the same tests used in the serological screening of blood donors. The blood recipients were divided into three groups: Group 1 (G1), patients who had never received blood, Group 2 (G2), patients who had received multiple transfusions and Group 3 (G3) one-off recipients. SPSS v.8 was used for statistical analysis. Values of p<0.05 were taken to be significant. The results showed that 62 blood recipients tested positively for one or more blood-borne infectious diseases. In addition, several recipients were unaware of their serological status before the transfusion. The identification of blood-borne infectious diseases in recipients before transfusion could avoid the State being held responsible by recipients who were unaware that they were carriers of such diseases and only found out about their contamination after transfusion.